Look closer [large type] - Ellis, David, 1967- (Thorndike Press large print core series., 2022)
"Simon and Vicky couldn't seem more normal: a wealthy Chicago couple, he a respected law professor, she an advocate for domestic violence victims. A stable, if unexciting marriage. But one thing's for sure ... absolutely nothing is what it seems. The pair are far from normal, and one of them just may be a killer. When the body of a beautiful socialite is found hanging in a mansion in a nearby suburb, Simon and Vicky's secrets begin to unravel. A secret whirlwind affair. A twenty-million-dollar trust fund about to come due. A decades-long grudge and obsession with revenge. These are just a few of the lies that make up the complex web...and they will have devastating consequences. And while both Vicky and Simon are liars, just who exactly is conning who? Part Gone Girl, part Strangers on a Train, Look Closer is a wild rollercoaster of a read that will have you questioning everything you think you know"--